Pertanggungjawaban Pidana Terhadap Pelaku Skizofrenia Dalam Pembunuhan Berencana (Studi Putusan Nomor: 150/Pid.B/2024/Pn Jkt. Brt) - Eki Prabitra Kenedy; Lusia Sulastri; Rahman Amin (Bhara Justisia, 2026)
This study examines the criminal responsibility of offenders with schizophrenia in cases of premeditated murder, with a focus on Decision of the West Jakarta District Court Number 150/Pid.B/2024/PN Jkt. Brt. The main objective of this research is to assess the conformity of the application of Article 44 of the Indonesian Criminal Code (KUHP) and the legal strength of medical evidence, particularly psychiatric expert testimony, in determining the defendant’s capacity for criminal responsibility. This research employs a normative juridical method using statutory, conceptual, and case approaches, analyzed qualitatively based on legal norms, doctrines, and judicial reasoning. The findings show that in Decision Number 150/Pid.B/2024/PN Jkt. Brt, the panel of judges, in rendering its verdict, did not fully apply the principles of criminal responsibility based on fault and capacity for responsibility as mandated by Article 44 of the former Criminal Code. Although the defendant, Andi Andoyo, was medically diagnosed with paranoid schizophrenia through a Visum et Repertum Psychiatricum, the court nevertheless concluded that he was criminally responsible solely because he was able to answer questions and appeared to understand his actions. This approach reflects a reduction of the concept of criminal responsibility to mere factual awareness, without adequately considering the defendant’s full psychological capacity to control his will and to comprehend the unlawful nature of his conduct. Furthermore, this study finds that the Visum et Repertum Psychiatricum and psychiatric expert testimony constitute lawful evidence under Article 184 of the Indonesian Code of Criminal Procedure (KUHAP). However, in Indonesian criminal justice practice, such medical evidence is often treated merely as supplementary and may be disregarded in favor of the judge’s personal conviction, as illustrated in Decision Number 150/Pid.B/2024/PN Jkt. Brt. The weak legal position of medical evidence directly contributes to errors in assessing the defendant’s criminal responsibility and leads to decisions that may be unjust and inconsistent with the principles of humanity and the protection of persons with mental disorders as provided in Article 44 of the former Criminal Code and Article 38 of the new Criminal Code